DOI: 10.14264/uql.2018.830
|View full text |Cite
|
Sign up to set email alerts
|

Building Design Optimization: Integration of Thermal and Fire Performance

Abstract: The main objective pursued by a fire safety strategy defined for a building design is to achieve an appropriate safe egress time required by the occupants under any fire scenario. This time must be shorter than the fire growth rate, profoundly influenced by the material flammability characteristics of building components. As witnessed in recent fire scenarios, this egress time can be severely compromised by the flammability of innovative building assemblies that include light and combustible materials which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(87 reference statements)
1
0
0
Order By: Relevance
“…Temperature readings at various locations through the cross section of a SIP heated from one side showed that EPS beads exhibited volumetric contraction at approximately 7 minutes after initiation of a constant 15 KW m -2 heat flux exposure (typical low range post-flashover exposure rates). Consistently with other experimental work [94], the critical temperature was established between 95°C and 100°C.…”
Section: Discussionsupporting
confidence: 91%
“…Temperature readings at various locations through the cross section of a SIP heated from one side showed that EPS beads exhibited volumetric contraction at approximately 7 minutes after initiation of a constant 15 KW m -2 heat flux exposure (typical low range post-flashover exposure rates). Consistently with other experimental work [94], the critical temperature was established between 95°C and 100°C.…”
Section: Discussionsupporting
confidence: 91%